(untitled) (Innovative professional education, 2025)
The mechanisms for ensuring the quality of professional education and training in the United Kingdom have been investigated in the context of contemporary challenges. The study highlights the regulatory and legal framework, core principles, and approaches that shape the quality assurance system for professional education and specialist training in this country. The roles of both state and non-state institutions in monitoring and evaluating educational standards are elucidated, along with the specifics of certification and accreditation procedures that ensure the alignment of specialist training with labor market demands. The experience of the United Kingdom is summarized as a potential benchmark for enhancing the professional education system in Ukraine.